SUCCESSFUL NLP - Lazarus, Jeremy, author 651739 (Richmond, United Kingdom : Crimson Publishing, 2010)
Whether you want to achieve more at work, enhance your relationships or boost your confidence, NLP (Neuro Linguistic Programming) can make it happen. We show you how to easily master NLP techniques to unleash your potential and achieve success. Written by a certified NLP Master Trainer, this realistic and simple tool kit can be applied to all areas of your life, enabling you to use language expertly, change behaviours and respond well in any situation.